Scientific Cooperation and the Co-production of Scientific Outcomes for Physical Activity Promotion: Results From a Transdisciplinary Research Consortium - Ferschl, Susanne; Till, Maike; Abu-Omar, Karim; Pfeifer, Klaus; Gelius, Peter (Frontiers in Public Health, 2021)
Background: To tackle complex societal challenges such as the high prevalence of physical inactivity, research funding is increasingly channeled toward cross-disciplinary research consortia. This study focused on exchange and cooperation (E&C) among the scientists of a 5-year transdisciplinary research initiative in Germany. Researchers' perceptions of E&C were combined with numbers of collaborative products during the project's life to make the developments of E&C and the quality of collaborative products visible. Methods: We applied a mixed-methods design including a qualitative content analysis of pre-interviews, focus-group interviews, and documents as well as a quantitative analysis of research (scientific publications, books, conference participations) and training outcomes (supervised bachelor's, master's, and Ph.D. theses). Inductive and deductive approaches were combined to analyze factors of collaborative readiness and to identify perceptions of E&C among project teams. Based on Hall et al.'s “Conceptual Model for Evaluation of Collaborative Initiatives,” the project period was separated into phases of “collaborative readiness,” “collaborative capacity,” and “collaborative products.” Results: Our findings revealed a discrepancy between the objectively assessed concepts of collaborative readiness and researchers' reported perceptions of E&C during the early project stage. A set of E&C hindering factors identified during the initial project phase remained present until the final project stage. Further, E&C among scientists increased over time, as reflected by researchers' perceptions. Reports of scientists also showed that outcomes were co-produced at the final project stage for the first time, while knowledge integration had not yet been achieved. Generally, the number of collaborative products (particularly scientific publications) also substantially increased over time. E&C was supported and promoted by the efforts of the coordinating sub-project. Conclusion: Scientific E&C is a learning process and needs time to develop. A participatory research approach taking into account the perspectives on and requirements for E&C during the project's design might lay the ground for suitable, supportive, and transparent conditions for effective and successful E&C. Despite their time- and resource-consuming nature, cross-disciplinary research initiatives provide a fertile context in which to generate new solutions for pressing societal issues given that long-term funding and the establishment of an overarching coordination organ is assured.